2021
DOI: 10.14218/jcth.2021.00021
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-7-5p Inhibits Migration, Invasion and Metastasis of Intrahepatic Cholangiocarcinoma by Inhibiting MyD88

Abstract: Background and Aims: Intrahepatic cholangiocarcinoma (ICC) is a malignant tumor derived from intrahepatic bile duct epithelial cells. Accumulating studies report that mi-croRNAs are widely involved in tumor migration and metastasis by regulation of target genes. miR-7-5p has been confirmed to inhibit tumor metastasis and to be related to prognosis for several malignant tumors. Our study investigated the underlying functions of miR-7-5p in ICC. Methods: The expression of miR-7-5p in ICC tissues but also in ICC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The roles of other miRNAs in CCA have been reported previously: there is upregulation of miR-181b-5p 22 and miR-23a-3p 23 in human CCA tissues and of miR-196-5p in CCA cell lines 24 . On the other hand, miRNA-206 is downregulated in CCA cell lines 25 , miR-7-5p in intrahepatic CCA tissue and cell lines 26 , and miR-451 in human tissues and serum 27 in CCA patients compared with normal subjects. As the most upregulated miRNA of the ten miRNAs previously reported to be elevated, miR-205-5p was more abundant in exosomes isolated from KKU-M213 and HuCCA-1 cell lines than in exosomes isolated from the H69 CCA cell line 28 .…”
Section: Introductionmentioning
confidence: 93%
“…The roles of other miRNAs in CCA have been reported previously: there is upregulation of miR-181b-5p 22 and miR-23a-3p 23 in human CCA tissues and of miR-196-5p in CCA cell lines 24 . On the other hand, miRNA-206 is downregulated in CCA cell lines 25 , miR-7-5p in intrahepatic CCA tissue and cell lines 26 , and miR-451 in human tissues and serum 27 in CCA patients compared with normal subjects. As the most upregulated miRNA of the ten miRNAs previously reported to be elevated, miR-205-5p was more abundant in exosomes isolated from KKU-M213 and HuCCA-1 cell lines than in exosomes isolated from the H69 CCA cell line 28 .…”
Section: Introductionmentioning
confidence: 93%
“…As for ICC, cancer tissue and HCCC-9810 cell line, the level of oncogenic miR-31 has been reported to significantly increase to target RAS p21 GTPase activating protein 1, and this promoted cell proliferation via Ras-MAPK signaling pathway [ 46 ]. Whereas, miR-7-5p has been shown to negatively regulate ICC cell proliferation, migration, and invasion via targeting myeloid differentiation factor 88 [ 47 ]. Also, miR-424-5p has been observed to target AMPK-related protein kinase 5; it is downregulated in ICC tissues and this stimulates the invasion, migration and EMT progression of ICC [ 48 ].…”
Section: Roles Of Dem-deg Network In Hepatocarcinogenesismentioning
confidence: 99%
“…Based on certain preclinical studies that have identified the potential therapeutic effects of drugs targeting the STaT signal transduction pathway, the development of highly effective and well-tolerated drugs is anticipated in the future. The molecular mechanism of icc requires further exploration (101), which will facilitate the application of specific genes and signalling pathways to the classification of icc molecular subtypes and the development of targeted therapeutic drugs. Further studies are required to take advantage of multidisciplinary comprehensive treatment, including surgery, chemotherapy and targeted therapy, according to the molecular characteristics of icc in order to improve the quality of life and prolong the survival time of patients.…”
Section: Summary and Prospectsmentioning
confidence: 99%